2005
DOI: 10.1590/s1413-86702005000400005
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiota of patients with bacterial infection of the respiratory tract treated with amoxicillin

Abstract: The intestinal tract harbors a huge diversity of metabolically-active aerobic and anaerobic bacteria that interact, forming a complex ecosystem. This microbiota has an important role in human metabolism, nutrition, immunity, and protection against colonization by pathogenic microorganisms. Several factors can influence the intestinal microbiota; these include age, diet, inflammatory and infectious processes, and the use of antimicrobials. We investigated the influence of bacterial infection of the respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 58 publications
(65 reference statements)
0
9
0
4
Order By: Relevance
“…Several studies have shown that orally administered antibiotics can significantly decrease Bacteroides counts (2,3,46). In fact, a decline in intestinal Bacteroides numbers has been reported after treatment with amoxicillin, a beta-lactam antibiotic that was also administrated to many of the patients in the current study (41).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Several studies have shown that orally administered antibiotics can significantly decrease Bacteroides counts (2,3,46). In fact, a decline in intestinal Bacteroides numbers has been reported after treatment with amoxicillin, a beta-lactam antibiotic that was also administrated to many of the patients in the current study (41).…”
Section: Discussionmentioning
confidence: 48%
“…In contrast, a molecular study assessing the fecal microbial populations of Crohn's disease patients revealed a relatively stable Bifidobacterium community (54). Many studies have reported an antibiotic-induced decrease in Bifidobacterium counts (3,16,41,46). Several Bifidobacterium strains are used as probiotics in healthy and diseased populations (47,64), but until now, only very few studies have assessed the effects of probiotics in patients with CF (6,7,70).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O uso combinado de zidovudina (AZT) com lamivudina (3TC) é recomendado na maioria das situações com indicação de uso de quimioprofilaxia. O uso do indinavir ou nelfinavir deve ser reservado para acidentes graves e situações em que haja possibilidade de resistência viral do paciente-fonte 14 . Há necessidade de se conhecer melhor as possíveis interações dessas drogas na microbiota intestinal e assim contribuir para o melhor seguimento desses indivíduos.…”
Section: Monreal Colsunclassified
“…O trato gastrointestinal possui enorme variedade de bactérias aeróbias e anaeróbias que interagem entre si em complexo ecosistema 14 . O cólon apresenta flora extremamente rica, com aproximadamente 400-500 espécies de microorganismos e de bactérias anaeróbias, destacando-se em ordem decrescente: bacteróides, bifidobactérias, lactobacillus entre outros 18 .…”
unclassified